2021
DOI: 10.1073/pnas.2017742118
|View full text |Cite
|
Sign up to set email alerts
|

Prior activation state shapes the microglia response to antihuman TREM2 in a mouse model of Alzheimer’s disease

Abstract: Triggering receptor expressed on myeloid cells 2 (TREM2) sustains microglia response to brain injury stimuli including apoptotic cells, myelin damage, and amyloid β (Aβ). Alzheimer’s disease (AD) risk is associated with the TREM2R47H variant, which impairs ligand binding and consequently microglia responses to Aβ pathology. Here, we show that TREM2 engagement by the mAb hT2AB as surrogate ligand activates microglia in 5XFAD transgenic mice that accumulate Aβ and express either the common TREM2 variant (TREM2CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…We first used published mouse data sets to determine the function of each cluster. Transcriptional signatures have been described for various microglia subclusters in murine models of disease, including neurodegenerative or disease-associated microglia (DAM), interferon-responsive (IFN-R), and antigen presenting (MHC-II high, MHCII+) related populations 17 . In contrast to murine models, these profiles did not discriminate as well between microglia from healthy and diseased patients.…”
Section: Resultsmentioning
confidence: 99%
“…We first used published mouse data sets to determine the function of each cluster. Transcriptional signatures have been described for various microglia subclusters in murine models of disease, including neurodegenerative or disease-associated microglia (DAM), interferon-responsive (IFN-R), and antigen presenting (MHC-II high, MHCII+) related populations 17 . In contrast to murine models, these profiles did not discriminate as well between microglia from healthy and diseased patients.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the potential therapeutic impact of targeting TREM2, we decided to generate single-chain variable antibody fragments (scFvs) against the human TREM2 ectodomain with which to study TREM2 structure and function. Agonist antibodies have already been reported in recently published work (Ellwanger et al, 2021;Fassler et al, 2021;Ibach et al, 2021;Price et al, 2020;Schlepckow et al, 2020;Wang et al, 2020). The group of Schlepckow have shown that a full-length antibody specific to mouse TREM2 can decrease shedding and activate TREM2 signaling in vitro, and also lead to a significant reduction in amyloid plaques in 6-month-old amyloid-beta precursor protein knockin mice (Schlepckow et al, 2020).…”
Section: Articlementioning
confidence: 99%
“…TREM2 manipulation, either through genetic deletion or antibody-dependent activation, may have different effects on pathology in various amyloid-and tau-expressing AD mouse models [152][153][154][155][156]. Soluble forms of TREM2 also appear to modulate AD pathology through direct action on microglial phenotypes [157,158].…”
Section: Inflammation and Polarizationmentioning
confidence: 99%
“…Specific microglial receptors, such as TREM2, provide an initial signal for DAM/MGnD activation by binding to ApoE [51,52,56]. Along these lines, recent studies have shown that humanized antibodies targeting TREM2 promote microglia activation, reduce pathology, correct cognitive deficits and dictate microglial responses even in AD mouse models carrying TREM2 variants [153,154,[226][227][228]. This is particularly important, as some TREM2 variants, such as TREM2-R47H [126], are considered loss-of-function mutations and are associated with worsened pathology in AD mouse models [62].…”
Section: Microglia Depletion and Targeting Microglial Receptors During Homeostasis And Diseasementioning
confidence: 99%